Sinergi Organisasi Perangkat Daerah dalam Pelaksanaan Perwal No. 13 Tahun 2012 untuk Pengembangan Wisata Sejarah Kesawan - Saut Manuntun Sitorus; Subhilhar Subhilhar; Nurman Achmad (Universitas Medan Area, 2025)
This study aims to analyze the synergy among Regional Apparatus Organizations (OPDs) in the implementation of Medan Mayor Regulation No. 13 of 2012 and to identify the obstacles faced in developing the Kesawan historical tourism area. Using a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and document analysis involving stakeholders from various agencies and local communities. The findings reveal that although there is a division of roles among the Tourism Office, Education Office, and Spatial Planning and Building Office, implementation remains sectoral and lacks systematic integration. Structural and cultural barriers, along with limited human resources and infrastructure, are the main challenges. This study recommends strengthening inter-agency synergy through the establishment of cross-sectoral collaborative forums, community participation, and adaptive and inclusive policy reform. These findings highlight the importance of collaborative governance as a strategic approach for the sustainable preservation of heritage areas.